Sejarah Side Dish Sebagai Budaya Hidangan Korea - Nindya, Assyifani (PT. Alahyan Publisher Sukabumi, 2024)
This research aims to describe the history of side dishes as a Korean dish. The method used in this research is a descriptive method. The collection technique comes from Korean films and dramas and references to theoretical studies into research journals. Data analysis techniques begin with data reduction, data presentation, conclusions and verification. The results of the analysis of how banchan or side dishes became Korean dish culture, starting from ancient times since the kingdom. There is also a reason why side dishes or banchan in Korea use fermented vegetables.